2007
DOI: 10.1111/j.1475-6811.2007.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential parenting and sibling jealousy: Developmental correlates of young adults’ romantic relationships

Abstract: Data from a survey of 200 young adults assessed whether the early nonshared environment, specifically parental differential treatment, was associated with romantic relationship distress through its effects on sibling jealousy, attachment styles, and self-esteem. Individuals who received equal affection from their parents in comparison to their sibling reported equal jealousy between themselves and their sibling, had higher self-esteem, more secure attachment styles, and less romantic relationship distress. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 75 publications
3
64
1
4
Order By: Relevance
“…It is the child's experience of differential parenting practices as unfair and inequitable that exacerbates the adverse effects of differential parenting on the quality of the sibling relationship. Parents' differential treatment of siblings has been hypothesized to contribute to variations in the quality of sibling relationships and has been conjectured to create negativity in their relationship by inducing feelings of rivalry, anger, and mistrust (Gilbert & Gerlsma, 1999;Rauer & Volling, 2007). Garcia, Shaw, Winslow, and Yaggi (2000) state that being the nonpreferred child increases that child's conflict with siblings during childhood.…”
Section: Unequal Parental Treatment Narcissism and Sibling Relationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is the child's experience of differential parenting practices as unfair and inequitable that exacerbates the adverse effects of differential parenting on the quality of the sibling relationship. Parents' differential treatment of siblings has been hypothesized to contribute to variations in the quality of sibling relationships and has been conjectured to create negativity in their relationship by inducing feelings of rivalry, anger, and mistrust (Gilbert & Gerlsma, 1999;Rauer & Volling, 2007). Garcia, Shaw, Winslow, and Yaggi (2000) state that being the nonpreferred child increases that child's conflict with siblings during childhood.…”
Section: Unequal Parental Treatment Narcissism and Sibling Relationmentioning
confidence: 99%
“…Disparities in parents' affection for and warmth toward different children in the family, and differences in how restrictive and punitive parents are toward each child, have been shown to undermine the quality of the sibling relationship during childhood and adolescence and to provoke hostile, coercive, and frequent conflict between siblings (Boer, Goedhart, & Treffers 1992;Brody, Stoneman, & McCoy, 1992;Feinberg, Reiss, Neiderhiser, & Hetherington, 2005;McHale, Crouter, & McGuire, 1995;McHale et al, 2000). Rauer and Volling (2007), who studied 200 young adults aged 18-22 years, reported that parental differential affection was strongly related to feelings of jealousy toward one's sibling.…”
Section: Unequal Parental Treatment Narcissism and Sibling Relationmentioning
confidence: 99%
See 2 more Smart Citations
“…also rodriguez, DiBello, overup and Neighbors (2015) concluded that anxious attachment moderates the association between trust and jealousy, which in turn affects satisfaction at the couple level (Dandurand & lafontaine, 2014). in addition, women who grew up without the presence of their father reported more anxious and preventive jealousy (Brummen-girigori, Buunk, Dijkstra, & girigori, 2016); and it is stated that jealousy may be mediated by differential affection -comparison with a sibling -during childhood (rauer & Volling, 2007) and the last children were more jealous than the firstborn (Buunk, 1997).…”
Section: Personal Variablesmentioning
confidence: 99%